On the lower estimate for k + 1-nondecomposible permutations - G. R. Chelnokov (Моделирование и анализ информационных систем)
A permutation т is сallеd k + 1-nondecomposible if the following condition holds: if {ai,..., ain} is a set of natural numbers such that 1